Reunited under the mistletoe - Meier, Susan (Harlequin romance, 2021)
"Autumn Jones is in shock after coming face-to-face with CEO Jack Adams again! How is she supposed to be his partner for their friends's glamorous winter wedding after the blush-inducing memories of their one amazing night together five years ago? But the minute they find themselves under the mistletoe, Autumn's plans to keep her cool start to melt--"--back cover.